Influence of Surface Treatment of Copper Substrates by Titanium Ions on Structure and Thermomechanical Properties of Nanocomposite Coatings on the Basis of Si-Al-N; Advanced Materials Research : Advanced materials, synthesis, development and application; Vol. 880 : Prospects of Fundamental Sciences Development (PFSD-2013) - Sergeev V. P. Viktor Petrovich; Fedorischeva M. V.; Neufeld V. V.; Kalashnikov M. P. (Chemistry and Physics of Materials Surface, 2014)
Title screen